Inheritance of cowpea resistance to flower thrips in Uganda germplasm - Agbahoungba, Symphorien; Karungi, Jeninah; Badji, Arfang; Sadik, Kassim; Gibson, Paul; Edema, Richard; Assogbadjo, Achille E.; Rubaihayo, Patrick R. (Journal of Plant Breeding and Crop Science, 2018)
Flower thrips [Megalurothrips sjostedti (Trybom)] is the most damaging insect pest on cowpea. However, information regarding the nature of gene action governing the inheritance of resistance to thrips is not available for cowpea genotypes in Uganda. This study was carried out to determine the inheritance pattern of cowpea resistance to flower thrips. Five resistant cowpea genotypes and three susceptible genotypes were crossed in full diallel mating design. F2 progenies were evaluated along with the parents in alpha lattice design with two replications under natural thrips infestation at Kabanyolo, Arua and Serere in Uganda. Combining ability analysis was performed using method one and model one of diallel analysis. The results showed that the environmental effects were highly significant (P<0.001). Additive, dominance and epistasis effects had major contributions. The broad sense heritability varied from 18 to 42% for thrips damage scores and from 0 to 6% for thrips counts. The estimates of narrow sense heritability were low for thrips damage score (2 to 18%) and thrips counts (0 to 9%). Genotypes TVU-1471 and TVU-1509 were identified as good transmitters of resistance to flower thrips. Crosses TVU-1509 x NE5, TVU-473 x Sanzi, TVU-123 x Sanzi, TVU-123 x TVU-473, and TVU-473 x TVU-1509 presented significant (P<0.05) and negative SCA effects for thrips damage scores and thrips counts and would be the most useful in breeding as some of their progenies would have high resistance to flower thrips. This study provides the basis of an efficient breeding program of cowpea for flower thrips resistance.
Keywords: Damage score; Gene action; Megalurothrips sjostedti; Vigna unguiculata